ANALISIS STATUS KEBERLANJUTAN AGROWISATA BERBASIS PERTANIAN BERKELANJUTAN: STUDI KASUS KEBUN STRAWBERRY UPANG - Santi Elvira; Ramadhani Eka Putra; Heri Rahman (University of Jember, 2022)
Agrotourism activities that are growing quite rapidly, making the competition for agrotourism in Upang Strawberry Farm quite high. In addition, the high increase in consumer demand make the production process directly proportional to use of the chemical products. This in the long term has the potential to threaten the sustainability of agrotourism. The application of the concept of sustainable agriculture in agrotourism is expected to overcome these sustainability problems. This study aims to determine the sustainability status of agrotourism in Upang Strawberry Farm. The analytical method used is Multidimensional Scaling (MDS) analysis and RAP-Agrotourism analysis tool. The results showed that the multidimensional Upang Strawberry Farm agrotourism had a less sustainable status (49,79%), based on the ecological dimension of 48,38% (less sustainable); economic dimension 53,61% (sufficiently sustainable); socio-cultural dimension 51,21% (sufficiently sustainable); institutional dimensions 49,19% (less sustainable) and facilities and infrastructure dimensions 46,42% (less sustainable).